Enhancing Stem Cell-Based Therapeutic Potential by Combining Various Bioengineering Technologies - Hong, In-Sun (Frontiers in Cell and Developmental Biology, 2022)
Stem cell-based therapeutics have gained tremendous attention in recent years due to their wide range of applications in various degenerative diseases, injuries, and other health-related conditions. Therapeutically effective bone marrow stem cells, cord blood- or adipose tissue-derived mesenchymal stem cells (MSCs), embryonic stem cells (ESCs), and more recently, induced pluripotent stem cells (iPSCs) have been widely reported in many preclinical and clinical studies with some promising results. However, these stem cell-only transplantation strategies are hindered by the harsh microenvironment, limited cell viability, and poor retention of transplanted cells at the sites of injury. In fact, a number of studies have reported that less than 5% of the transplanted cells are retained at the site of injury on the first day after transplantation, suggesting extremely low (< 1%) viability of transplanted cells. In this context, 3D porous or fibrous national polymers (collagen, fibrin, hyaluronic acid, and chitosan)-based scaffold with appropriate mechanical features and biocompatibility can be used to overcome various limitations of stem cell-only transplantation by supporting their adhesion, survival, proliferation, and differentiation as well as providing elegant 3-dimensional (3D) tissue microenvironment. Therefore, stem cell-based tissue engineering using natural or synthetic biomimetics provides novel clinical and therapeutic opportunities for a number of degenerative diseases or tissue injury. Here, we summarized recent studies involving various types of stem cell-based tissue-engineering strategies for different degenerative diseases. We also reviewed recent studies for preclinical and clinical use of stem cell-based scaffolds and various optimization strategies.